Penggunaan Media Pembelajaran Digital Untuk Meningkatkan Hasil Belajar Seni Budaya (Tari) di Kelas VIII A SMP Negeri 17 Kerinci - Andini Ade Nengsih; Alrizka Hairi Dilfa (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research sought to ascertain and characterize how the use of digital learning resources improved the dance learning outcomes of Class VIII SMPN 17 Kerinci pupils. Class action research (PTK), a subset of qualitative research, is the kind of study that this is. The researcher is the primary instrument in this study, with the help of supporting instruments in the form of written assessments (cognitive). Twenty-five pupils from class VIII A at SMP Negeri 17 Kerinci served as the study's subjects. Two cycles of planning, execution, observation, and reflection were employed in this study. The findings demonstrated that using digital learning resources to teach dance may enhance student learning outcomes. Due to the fact that many pupils still do not take learning seriously, cycle I learning has not been successfully implemented; cycle II learning continues this education. Cycle II learning has been implemented with good execution. Nearly all of the tasks at each level are completed, and students are actively engaged in their education, increasing the quality of their learning results. The average student learning results from written tests during cycle I were 56%, whereas the average student learning outcomes during cycle II were 84%. Applying digital learning media to dance education has been shown to improve student learning results, according to data analysis and debate.